АЗИ-НОМХОН ДАЛАЙН ОРНУУДЫН ХАМТЫН АЖИЛЛАГААНЫ БАЙГУУЛЛАГЫН ХӨГЖИЛ, ТӨЛӨВ /АПЕК/ - Р.ДАВААНЯМ (Politology, 2023)
Since the formation of APEC formed has been paid to the creation of free trade. As a result of the cooperation of the world’s most rapidly developing economies in the region to stay. APEC policy each further expand the range of its activities and a pioneer of the Asia-Pacific Economic Cooperation have become influential the process.